1991
DOI: 10.1093/oxfordjournals.eurheartj.a059875
|View full text |Cite
|
Sign up to set email alerts
|

Aortic root complications of infective endocarditis—influence on surgical outcome

Abstract: Fifty cases of aortic valve endocarditis during a 6-year period between 1982 and 1988 were reviewed. Twenty-three (46%) had aortic root complications by way of aortic root abscess or mycotic aneurysm in the perivalvular area. Patients with root complications were grouped into the aortic root abscess (ARA) group and those without into a non root abscess (NARA) group. Prosthetic valve endocarditis dominated in the ARA group (12 and four cases of prosthetic valve infection in the ARA and NARA groups, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…This finding—already described in a series reported by John et al ,13 who observed residual aortic regurgitation in 57% of patients with an aortic ring abscess compared with 8.7% of those without ring abscess—should argue for more radical or specific surgical approaches in patients with paravalvar abscesses. Recently, Glazier et al described their results using antibiotic impregnated homograft aortic root replacement with reimplantation of the coronary arteries14; in-hospital mortality was high (30%), but event-free survival at five years in hospital survivors was excellent (81%).…”
Section: Discussionsupporting
confidence: 59%
“…This finding—already described in a series reported by John et al ,13 who observed residual aortic regurgitation in 57% of patients with an aortic ring abscess compared with 8.7% of those without ring abscess—should argue for more radical or specific surgical approaches in patients with paravalvar abscesses. Recently, Glazier et al described their results using antibiotic impregnated homograft aortic root replacement with reimplantation of the coronary arteries14; in-hospital mortality was high (30%), but event-free survival at five years in hospital survivors was excellent (81%).…”
Section: Discussionsupporting
confidence: 59%
“…However, in a recent French multicentre survey, 12 the in-hospital mortality was similar in patients treated surgically (23%) and medically (18%). Though the operative mortality is high, ranging from 11% to 30%, [13][14][15] in our series it was not significantly diVerent from aortic endocarditis without ring abscess.…”
Section: Discussionmentioning
confidence: 46%
“…'4 15 Our study shows that transoesophageal echocardiographic imaging greatly facilitated the preoperative and post-operative diagnosis and management of aortic root abscesses in our patients and that the availability of biplane imaging offered considerably more information compared with monoplane imaging. To the best of our knowledge, this is the largest reported series of patients in whom transoesophageal echocardiography was used for the detection of an aortic root abscess and in which most of the patients underwent biplane or multiplane examination.…”
Section: Discussionmentioning
confidence: 75%